Antioxidant and Immune-Related Implications of Minerals in COVID-19: A Possibility for Disease Prevention and Management - Juan M. Toledano; María Puche-Juarez; Jorge Moreno-Fernandez; Julio J. Ochoa; Javier Diaz-Castro (MDPI AG, 2023)
Since the coronavirus disease 2019 (COVID-19) pandemic appeared, both governments and the scientific community have focused their efforts on the search for prophylactic and therapeutic alternatives in order to reduce its effects. Vaccines against SARS-CoV-2 have been approved and administered, playing a key role in the overcoming of this situation. However, they have not reached the whole world population, and several doses will be needed in the future in order to successfully protect individuals. The disease is still here, so other strategies should be explored with the aim of supporting the immune system before and during the infection. An adequate diet is certainly associated with an optimal inflammatory and oxidative stress status, as poor levels of different nutrients could be related to altered immune responses and, consequently, an augmented susceptibility to infections and severe outcomes derived from them. Minerals exert a wide range of immune-modulatory, anti-inflammatory, antimicrobial, and antioxidant activities, which may be useful for fighting this illness. Although they cannot be considered as a definitive therapeutic solution, the available evidence to date, obtained from studies on similar respiratory diseases, might reflect the rationality of deeper investigations of the use of minerals during this pandemic.